Policies for new energy challenges - Ferreira, Paula Varandas (2020)
This special issue presents some of the latest energy planning-related research as presented at the 2019 International Conference on Energy & Environment (ICEE), University of Minho, Portugal, 2019. In this issue, work is presented which investigates policy initiatives’ effects on electricity prices. Other authors apply Modern Portfolio Theory to analyse the energy and environmental policies of the European Union member states. Solar thermal systems are analysed based on a novel costing methodology and lastly carbon dioxide emissions from a Portuguese energy system with further deployment of electric vehicles are assessed.